Clinically meaningful effect of strontium ranelate on symptoms in knee osteoarthritis: a responder analysis. - Bruyère, O; Reginster, J; Bellamy, N; Chapurlat, R; Richette, P; Cooper, C (2014)
OBJECTIVES: The aim of this study was to assess the efficacy of strontium ranelate in improving symptoms in knee OA. METHODS: Symptoms were assessed over 3 years in patients with primary knee OA receiving strontium ranelate 2 g/day (n = 454), 1 g/day (n = 445) or placebo (n = 472) in the Strontium Ranelate Efficacy in Knee Osteoarthritis Trial. Clinical response was evaluated using WOMAC subscores, minimal perceptible clinical improvement (MPCI), minimal clinically important improvement (MCII) and a modified OMERACT-Osteoarthritis Research Society International (OARSI) responder definition. Patients who withdrew prematurely from the study were considered non-responders. RESULTS: There was no significant effect on symptoms for strontium ranelate 1 g/day. At the dosage of 2 g/day, strontium ranelate was associated with greater response than placebo in terms of ≥20% improvement in WOMAC pain from baseline to the last visit (58% vs 47%, P = 0.002) and ≥50% improvement in WOMAC pain (42% vs 36%, P = 0.083). Significant differences were found in MPCI response for WOMAC pain (52% vs 40%, P < 0.001), stiffness (47% vs 39%, P = 0.009) and physical function (46% vs 37%, P = 0.009) and in MCII response for WOMAC physical function (46% vs 37%, P = 0.013). There were also more OMERACT-OARSI-like responders with strontium ranelate (44% vs 35%, P = 0.004). The treatment-placebo difference in MPCI response for WOMAC pain was significant after 6 months (P = 0.024), while that in MPCI and MCII response for WOMAC physical function reached significance after 12 months (P = 0.027 and P = 0.019, respectively). CONCLUSION: Treatment with strontium ranelate 2 g/day over 3 years is associated with a clinically meaningful improvement in pain from 6 months as well as physical function and stiffness as assessed by the number of responders above thresholds of clinical relevance. TRIAL REGISTRATION: Current Controlled Trials. http://www.controlled-trials.com/ (ISRCTN41323372).